Breastfeeding Is Associated with Decreased Risk of Hospitalization among HIV-Exposed, Uninfected Kenyan Infants. (August 2016) - Ásbjörnsdóttir, Kristjana H.; Slyker, Jennifer A.; Maleche-Obimbo, Elizabeth; Wamalwa, Dalton; Otieno, Phelgona; Gichuhi, Christine M.; John-Stewart, Grace
Background: Human immunodeficiency virus (HIV)–exposed uninfected (HEU) infants are a growing population in sub-Saharan Africa, with higher morbidity and mortality than HIV-unexposed infants. HEU infants may experience increased morbidity due to breastfeeding avoidance. Objectives: We sought to describe the burden and identify predictors of hospitalization among HEU infants in the first year of life. Methods: Using a retrospective cohort of HIV-infected mothers and their HEU infants in Nairobi, Kenya, we identified infants who were HIV-uninfected at birth and were followed monthly until their last negative HIV test, death, loss to follow-up, or study exit at 1 year of age. Incidence, timing, and reason for hospitalization was assessed overall as well as stratified by feeding method. Predictors of first infectious disease hospitalization were identified using competing risk regression, with HIV acquisition and death as competing risks. Results: Among 388 infants, 113 hospitalizations were reported (35/100 infant-years [the combined years of observation contributed by all infants in the study]; 95% confidence interval [CI], 29-42). Ninety hospitalizations were due to 1 or more infectious diseases (26/100 infant-years; 95% CI, 21-32)—primarily pneumonia (n = 40), gastroenteritis (n = 17), and sepsis (n = 14). Breastfeeding was associated with decreased risk of infectious disease hospitalization (subhazard ratio = 0.39; 95% CI, 0.24-0.64), as was time-updated nutrition status (subhazard ratio = 0.73; 95% CI, 0.61-0.89). Incidence of infectious disease hospitalization among formula-fed infants was 51/100 infant-years (95% CI, 37-70) compared to 19/100 infant-years (95% CI, 14-25) among breastfed infants. Conclusion: Among HEU infants, breastfeeding and nutrition status were associated with reduced hospitalization during the first year of life.